Effects of boron content on the microwave‐transparent property and high‐temperature stability of continuous SiBN fibers. Issue 8 (6th May 2020) - Long, Xin; Shao, Changwei; Wang, Yingde
Abstract: Owing to their high‐temperature stability and microwave‐transparent properties, SiBN fibers are promising reinforcement materials for microwave windows or radomes in harsh environments. This work investigates the high‐temperature properties of continuous SiBN fibers with different boron contents. Compared with Si3 N4 fibers, the SiBN fibers demonstrated superior high‐temperature stability, retaining their original tensile strength up to 1600°C with a smooth surface and amorphous structure. The boron‐containing microstructure improved the microwave‐transparent properties of the SiBN fibers by decreasing their dielectric constant and loss. The values were stabilized at temperatures up to 1200°C. The high‐temperature stability and microwave transparency of the SiBN fibers were likely contributed by the synergistic effect of the amorphous BN phase and the Si–N–B networks (the main existing state of the boron atoms). Abstract : Continuous SiBN fibers could remain tensile strength up to 1600°C.